Clinical and Magnetic Resonance Imaging (MRI) Distinctions Between Tumefactive Demyelination and Brain Tumors in Children. (May 2014) - Yiu, Eppie M.; Laughlin, Suzanne; Verhey, Leonard H.; Banwell, Brenda L.; ,
Tumefactive demyelinating lesions can be difficult to distinguish from tumors. Clinical and magnetic resonance imaging features of children with tumefactive demyelination and supratentorial brain tumors were compared. Patients were identified through a 23-site national demyelinating disease study, and from a single-site neuroradiology database. For inclusion, lesions met at least 1 of 3 criteria: maximal cross-sectional diameter >20 mm, local or global cerebral mass effect, or presence of perilesional edema. Thirty-one children with tumefactive demyelination (5 with solitary lesions) were identified: 27 of 189 (14.3%) from the demyelinating disease study and 4 from the database. Thirty-three children with tumors were identified. Children with tumefactive demyelination were more likely to have an abnormal neurologic examination and polyfocal neurologic deficits compared to children with tumors. Tumefactive demyelination was distinguished from tumor by the presence of multiple lesions, absence of cortical involvement, and decrease in lesion size or detection of new lesions on serial imaging.